1998
DOI: 10.1890/1051-0761(1998)008[0228:smfeci]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Sampling Methods for Estimating Change in Forest Resources

Abstract: Changes in forest resources have been estimated in a variety of ways. This paper focuses on extensive forest surveys rather than on sentinel‐site investigations. The sampling design and plot design used are key to precise estimates of change. Alternative sampling designs include temporary surveys, Continuous Forest Inventory, and Sampling with Partial Replacement. Each can be used in conjunction with stratified sampling or double sampling for stratification. Plot designs can involve variable‐radius or Bitterli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(40 citation statements)
references
References 7 publications
0
33
1
1
Order By: Relevance
“…Plot size is a key factor determining the accuracy of statistical estimations of parameters (Scott 1998). Our results showed a significant effect of plot size on univariate and bivariate spatial structure parameters.…”
Section: Optimum Plot Sizementioning
confidence: 59%
See 1 more Smart Citation
“…Plot size is a key factor determining the accuracy of statistical estimations of parameters (Scott 1998). Our results showed a significant effect of plot size on univariate and bivariate spatial structure parameters.…”
Section: Optimum Plot Sizementioning
confidence: 59%
“…Kangas (2006) concluded that the coefficient of variation increases with decreasing plot size, which is consistent with our results. Similarly, Scott (1998) found that as plot size increases, within-plot variance increases and between-plot variance decreases, resulting in a smaller variance estimate across all plots. The bivariate spatial analyses for each sample in our study suggest a random spatial distribution for Isoberlinia spp.…”
Section: Optimum Plot Sizementioning
confidence: 79%
“…The disadvantage of this method is that it requires extensive biotic surveys, which in turn may require substantial investment of resources (Longino andColwell 1997, Mac Nally 1997). Identification of umbrella species could reduce the sampling effort necessary to prioritize areas for protection or other land uses, because it usually is faster and cheaper to sample a subset of a taxonomic group than to survey all members of the group (Scott 1998). Umbrella species have limited application in landscapes where practitioners are interested in shortcuts to assess ecosystem integrity for purposes of land management.…”
Section: Introductionmentioning
confidence: 99%
“…A fundamental part of this in both Nigeria and Ghana is expert work at rendering carbon visible through maps, figures, charts. Often, these activities render carbon visible by rendering other things invisible, drawing on similar historic, simplifying forestry logic that produced bio-diverse landscapes as timber [98,99]. While these representations are informing mass education and mobilisation in Ghana, in Nigeria carbon representations are being uneasily territorialised through superimposition of significantly simplified images of carbon forests on actual, dynamic forest landscapes.…”
Section: Discussionmentioning
confidence: 99%